Feel Good? The Dialectical Integration of International Immigrants in Rural Communities: The Case of the Canadian Prairie Provinces - Dauphinais, Jennifer; Salmon, Sherine; Akimowicz, Mikaël (Frontiers in Sociology, 2021)
The increasing influx of international immigrants settling in rural communities, where their landing is expected to revitalize communities, has triggered concerns about international immigrants' adaptation and well-being. In this article, we specifically focus on international immigrants' economic integration as a part of their socialization in communities. This article integrates the results of two independent studies, respectively, focusing on rural employers' motivations to hire immigrants and immigrants' integration in rural communities, both taking place in the Canadian Prairie provinces. Based on a survey of 112 employers and 36 in-depth interviews with international immigrants and organizations promoting their integration, we explore the impact of mediating organizations on the well-being of international immigrants. The results highlight that mediating organizations facilitate the sharing of meanings between rural communities' stakeholders, which is key to success for both employers and employees in formalized organizations such as businesses. The results suggest that international immigrants' well-being is facilitated by mediating organizations that foster a dialectical transformation of rural communities where both hosts and immigrants understand each other.